Magnesium-doped and carbon nanotube dual-modified lithium manganese iron phosphate material and preparation method thereof
Through magnesium doping and carbon nanotube modification of lithium manganese iron phosphate material, the energy density and cycle stability problems of lithium manganese iron phosphate material in lithium-ion batteries are solved, and higher battery performance is achieved.
Patent Information
- Application Number
- CN202510514644.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-23
- Publication Date
- 2025-08-29
- Estimated Expiration
- 2045-04-23
AI Technical Summary
The energy density and cyclic stability of lithium manganese iron phosphate materials in lithium-ion batteries are limited by the problems of voltage platform, compaction density and poor conductivity.
The dual modification strategy of magnesium doping and carbon nanotubes is adopted to generate lithium manganese iron phosphate material in situ through hydrothermal reaction, and a three-dimensional conductive network is constructed with a magnesium source and carbon nanotubes to optimize the structural stability and conductivity of the material.
It improves the energy density and cycle life of lithium batteries, improves the conductivity of the material and the diffusion rate of lithium ions, reduces polarization and enhances electrochemical properties.
Smart Images

Figure CN120553661A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a magnesium-doped and carbon nanotube-double-modified lithium manganese iron phosphate material and a preparation method thereof. Background Art
[0002] Lithium iron manganese phosphate (LFMP) has become a highly promising cathode material in the field of lithium-ion batteries due to its high voltage platform (~4.1V), excellent thermal stability and low cost, but its practical application is limited by the energy density bottleneck.
[0003] On the one hand, the dual voltage platform (Fe / Mn redox reaction) leads to high-voltage decomposition of the electrolyte and capacity decay, and the structural degradation caused by manganese dissolution further weakens the cycle stability; on the other hand, the material has poor intrinsic conductivity and low compaction density of nanoparticles (1.8-2.3g / cm 3 ) significantly reduces the volume energy density.
[0004] In the current study, the lattice doping of lithium manganese iron phosphate was modified by introducing heterogeneous ions. In addition, to address the agglomeration problem during the synthesis process, in-situ carbon-based materials (such as carbon nanotubes and graphene) were used to construct a three-dimensional interconnected conductive network, and the network pores were used to provide lithium ion diffusion channels inside the agglomerates, thereby weakening the negative impact of agglomeration on the electrode kinetic performance. However, although the above modification strategy has improved the cycle life and discharge specific capacity of LFMP, its energy density is still limited by the intrinsic voltage platform (~4.1V) and compaction density (<2.5g / cm 3 )’s inherent bottleneck. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a magnesium-doped and carbon nanotube-double-modified lithium manganese iron phosphate material and a preparation method thereof.
[0006] The technical solution of the present invention to solve the above technical problems is as follows:
[0007] The present invention provides a preparation method of a magnesium-doped and carbon nanotube-modified lithium iron manganese phosphate material. The method comprises preparing a mixed solution using a magnesium source component, a phosphorus source component, a manganese source component, an iron source component and a lithium source component. The mixed solution is mixed with carbon nanotubes, and the lithium iron manganese phosphate material is generated in situ through a hydrothermal reaction.
[0008] On the basis of the above technical solution, the present invention can also be improved as follows.
[0009] Furthermore, the molar percentage of the magnesium source component is 0.1-3 mol% of the phosphorus source component.
[0010] Furthermore, the magnesium source component includes at least one of magnesium sulfate, magnesium carbonate, and magnesium acetate.
[0011] Furthermore, based on the mass of the theoretically generated lithium manganese iron phosphate material being 100%, the mass percentage of the carbon nanotubes is 0.05 wt % to 2 wt %.
[0012] Furthermore, the lithium source component includes at least one of lithium carbonate, lithium acetate, lithium hydroxide, and lithium dihydrogen phosphate; the phosphorus source component includes at least one of phosphoric acid, ammonium dihydrogen phosphate, and lithium dihydrogen phosphate; the manganese source component includes at least one of manganese oxalate, manganese sulfate, and manganese acetate; and the iron source component includes at least one of ferrous oxalate, ferrous acetate, and ferrous sulfate; wherein the molar ratio of lithium to phosphorus is 1:1 to 3:1, and the molar ratio of the manganese source to the iron source is 5:5 to 9:1.
[0013] Further, the following steps are included:
[0014] S1, adding the phosphorus source solution dropwise to the lithium source solution to obtain solution A;
[0015] S2, mixing the iron source solution, the magnesium source solution and the manganese source solution to obtain solution B;
[0016] S3, adding the solution B dropwise to the solution A to obtain a first mixed solution, and adding the carbon nanotubes to the first mixed solution to obtain a second mixed solution;
[0017] S4, heating the second mixed solution and performing the hydrothermal reaction to obtain a reactant;
[0018] S5, washing, drying and grinding the precipitate in the reactant to obtain the lithium manganese iron phosphate powder;
[0019] S6. Sintering the lithium manganese iron phosphate powder to obtain the material.
[0020] Furthermore, in step S4, the hydrothermal reaction is to introduce the second mixed solution into a polytetrafluoroethylene liner, heat and react in a sealed stainless steel environment to obtain the reactant; the temperature of the heating reaction is 160-200° C., and the time is 8-16 hours.
[0021] Furthermore, in step S6, the lithium manganese iron phosphate powder is mixed with a carbon source and then sintered. The sintering conditions are: annealing at a temperature of 500-700° C. for 1-6 hours in an inert atmosphere.
[0022] The present invention also provides a magnesium-doped and carbon nanotube-double-modified lithium manganese iron phosphate material, which is prepared by the above method.
[0023] The present invention also provides a lithium battery, wherein the positive electrode material of the lithium battery is the lithium iron manganese phosphate material as described above.
[0024] The beneficial effects of the present invention are:
[0025] (1) The preparation method of the magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate material of the present invention, Mg 2+ Doping optimizes the bulk structural stability of the material, relieves lattice stress and increases the lithium ion diffusion rate;
[0026] (2) The preparation method of the magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate material of the present invention utilizes a three-dimensional conductive network constructed by CNTs to connect the internal particles of the agglomerated particles with the outside world.
[0027] (3) The preparation method of the magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate material of the present invention utilizes the high aspect ratio and mechanical strength of CNTs to construct a fast conductive skeleton that penetrates the electrode, and cooperates with Mg 2+ The lattice stabilization effect reduces polarization and improves rate performance;
[0028] (4) The preparation method of the magnesium-doped and carbon nanotube-double-modified lithium manganese iron phosphate material of the present invention adopts a double modification strategy to effectively improve the energy density and cycle life of the battery, and its application in lithium batteries will have excellent electrochemical performance;
[0029] (5) The preparation method of the magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate material of the present invention is simple and easy to control, and the entire process is green and environmentally friendly;
[0030] (6) The magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate material of the present invention has less capacity decay and higher coulombic efficiency, and also has good lithium ion transmission effect, and the capacity is greatly improved;
[0031] (7) The energy density and cycle life of the lithium battery of the present invention are effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The preparation method of the magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate composite material of the present invention, the XRD pattern of the embodiment, Figure 1 a is the overall XRD pattern of LFMMP-CNTs. Figure 1 b in the middle is Figure 1 A partial enlarged view of a in the middle;
[0033] Figure 2 The preparation method of the magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate composite material of the present invention, the SEM image of the embodiment, Figure 2 The scale bar in a is 200 nm. Figure 2 The scale bar in middle b is 1 μm;
[0034] Figure 3The preparation method of the magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate composite material of the present invention, the electrochemical test results of the embodiment and the comparative example, Figure 3 Figure a is the rate performance test diagram of two samples. Figure 3 Figure b is the first cycle charge and discharge curve of two samples at a current density of 0.1C. Figure 3 Figure c is the cycling performance curve of the two samples at 1C current density. DETAILED DESCRIPTION
[0035] The principles and features of the present invention are described below with reference to the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0036] The method for preparing the magnesium-doped and carbon nanotube-modified lithium iron manganese phosphate material of the present invention comprises preparing a mixed solution with a magnesium source component, a phosphorus source component, a manganese source component, an iron source component and a lithium source component, mixing the mixed solution with carbon nanotubes, and in-situ generating the lithium iron manganese phosphate composite material through a hydrothermal reaction.
[0037] The preparation method of the present invention, doping Mg 2+ The carbon nanotubes (CNTs) are in situ grown and composited with the positive electrode material, Mg 2+ Doping optimizes the material's bulk structural stability, relieves lattice stress and increases lithium ion diffusion rate. The three-dimensional conductive network constructed by CNTs connects the internal particles of the agglomerated particles with the outside world. The high aspect ratio and mechanical strength of CNTs are used to construct a fast conductive skeleton that penetrates the electrode, cooperating with Mg 2+ The lattice stabilization effect can further reduce polarization and improve rate performance; the preparation method of the present invention adopts the above-mentioned double modification strategy to effectively improve the energy density and cycle life of the battery, and its application in lithium batteries will have excellent electrochemical properties.
[0038] Specifically, Mg 2+ The effects of doping are as follows:
[0039] (1) Regulating lattice parameters: Incorporating Mg ions with a smaller radius into the Fe / Mn position can extend the Li-O bond, increase the interstitial position in the octahedral LiO6, and stabilize the olivine structure during the lithium insertion and extraction process, thereby achieving Li + Fast transmission.
[0040] (2) Inhibit lattice distortion: Mg’s strong oxygen affinity (high Mg-O bond energy) can stabilize PO4 3- Tetrahedral structure, which relieves the Li + The lattice stress caused by deintercalation reduces volume expansion, thereby enhancing the stability of lithium manganese iron phosphate.
[0041] (3) Enhanced electronic conductivity: Mg 2+ Doping may introduce lattice defects (such as cation vacancies or interstitial ions), forming localized electronic states and improving intrinsic electronic conductivity; Mg 2+ Doping can adjust the redox potential of Fe / Mn and inhibit the 3+ The disproportionation reaction (Mn 3+ →Mn 2+ +Mn 4+ ), reducing the structural distortion caused by the Jahn-Teller effect and maintaining the stability of the electron transmission path.
[0042] However, simply introducing magnesium cannot prevent the agglomeration of the resulting LFMP nanoparticles. This agglomeration leads to insufficient contact between the agglomerated particles and the electrolyte, resulting in capacity loss in the LFMP material. Simply adding conductive CNTs after LFMP synthesis, while enhancing the conductivity between the nanoparticles, does not improve the intrinsic conductivity of LFMP.
[0043] Because, in order to improve the electrical conductivity and lithium conductivity, the present invention adopts Mg 2+ After doping and LFMP synthesis, the addition of conductive CNTs creates a dual modification, enhancing both the external and intrinsic conductivity of the material. In-situ synthesis of LFMP on CNTs mitigates the effects of LFMP agglomeration, while the CNTs also act as a conductive agent to enhance the conductivity between the materials.
[0044] The conventional method of adding conductive agents is to add them after LFMP synthesis, but this method does not work on LFMP agglomeration because LFMP has already occurred during synthesis. Therefore, this method can only increase the conductivity between particles.
[0045] Therefore, in the preparation method of the present invention, LFMP nanoparticles are directly grown on the surface of CNTs to form an alternative covering agglomeration.
[0046] Preferably, the molar percentage of the magnesium source component of the present invention is 0.1-3 mol % of the phosphorus source component.
[0047] Preferably, the magnesium source component includes at least one of magnesium sulfate, magnesium carbonate, and magnesium acetate.
[0048] Preferably, based on the mass of the theoretically generated lithium manganese iron phosphate material being 100%, the mass percentage of the carbon nanotubes is 0.05 wt % to 2 wt %.
[0049] Preferably, the lithium source component includes at least one of lithium carbonate, lithium acetate, lithium hydroxide, and lithium dihydrogen phosphate; the phosphorus source component includes at least one of phosphoric acid, ammonium dihydrogen phosphate, and lithium dihydrogen phosphate; the manganese source component includes at least one of manganese oxalate, manganese sulfate, and manganese acetate; and the iron source component includes at least one of ferrous oxalate, ferrous acetate, and ferrous sulfate.
[0050] Preferably, the molar ratio of lithium to phosphorus is 1:1 to 3:1, and the molar ratio of the manganese source to the iron source is 5:5 to 9:1.
[0051] The preparation method of the present invention is specific and comprises the following steps:
[0052] S1. Add the phosphorus source solution dropwise to the lithium source solution to obtain solution A.
[0053] S2. Mix the iron source solution, the magnesium source solution, and the manganese source solution to obtain solution B.
[0054] Preferably, the lithium source solution is a water-ethylene glycol solution of lithium hydroxide, the phosphorus source solution is a phosphoric acid ethylene glycol solution, the iron source solution is an ethylene glycol solution of FeSO4·7H2O, and the manganese source solution is a water-ethylene glycol solution of MnSO4·H2O.
[0055] S3. Add solution B dropwise to solution A to obtain a first mixed solution, and add CNTs to the first mixed solution to obtain a second mixed solution.
[0056] Preferably, the CNTs may be pretreated first. The pretreatment method is as follows: weigh a certain amount of commercial CNTs, add ethylene glycol, vigorously stir and ultrasonically treat, each repeated three times, place the dispersed material in a stainless steel reactor, keep warm at 180°C for 5 hours, cool naturally, filter the resulting solution, and repeatedly wash and dry with anhydrous ethanol and deionized water to obtain pretreated CNTs.
[0057] S4. Heating the second mixed solution and performing a hydrothermal reaction to obtain a reactant.
[0058] Preferably, the hydrothermal reaction is to introduce the second mixed solution into a polytetrafluoroethylene liner, heat and react in a sealed stainless steel environment to obtain a reactant; the heating reaction temperature is 160 to 200° C., and the time is 8 to 16 hours.
[0059] S5. Washing, drying and grinding the precipitate in the reactants to obtain lithium manganese iron phosphate powder;
[0060] S6. Sintering the lithium manganese iron phosphate powder to obtain a composite material.
[0061] Preferably, the lithium manganese iron phosphate powder is mixed with a carbon source and then sintered. The sintering conditions are: annealing at a temperature of 500 to 700° C. for 1 to 6 hours in an inert atmosphere.
[0062] Preferably, the carbon source is at least one of glucose and sucrose.
[0063] More preferably, the mass of the carbon source is 0 to 30 wt % of the mass of the composite material powder.
[0064] The preparation method of the present invention has a simple and easy-to-control process, and the entire process is green and environmentally friendly.
[0065] The magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate composite material of the present invention has less capacity attenuation and higher coulombic efficiency, has good lithium ion transmission effect, and has greatly improved capacity.
[0066] The lithium battery of the present invention has a positive electrode material of the above-mentioned lithium manganese iron phosphate composite material; the energy density and cycle life of the lithium battery can be effectively improved.
[0067] The following is an illustration through specific examples and comparative examples.
[0068] Example
[0069] In this embodiment, the method of the present invention is used to prepare Mg 2+ The specific preparation process of the LFMP composite material doped with CNTs and modified with LFMP is as follows:
[0070] (1) Pretreatment of carbon nanotubes:
[0071] A certain amount of commercial carbon nanotubes was weighed and placed in a beaker. 60 ml of ethylene glycol was added. The above solution was vigorously stirred and ultrasonically treated, each repeated three times. The dispersed material was placed in a stainless steel reactor and kept at 180°C for 5 hours. The temperature was naturally cooled, and the resulting solution was filtered and repeatedly washed with anhydrous ethanol and deionized water. The obtained CNTs were dried.
[0072] (2) Raw material mixing:
[0073] Weigh 30mmol of LiOH, 11mmol of H3PO4, 2mmol of FeSO4·7H2O and 8mmol of MnSO4·H2O; replace an equal amount of ferrous sulfate with magnesium sulfate according to a 1% mass fraction so that the molar ratio of Li, Fe, Mg, Mn and P meets the requirements of LiFe 0.19 Mg 0.01 Mn 0.8 PO4.
[0074] LiOH was dissolved in a mixed solution of 2 ml of water and 20 ml of ethylene glycol to obtain a lithium source solution; H3PO4 was dispersed in 20 ml of ethylene glycol to obtain a phosphorus source solution; FeSO4·7H2O was dissolved in 10 ml of ethylene glycol to obtain an iron source solution; MnSO4·H2O was dispersed in a mixed solution of 3 ml of water and 10 ml of ethylene glycol to obtain a manganese source solution.
[0075] The H3PO4 solution is added dropwise to the LiOH solution to form solution A; FeSO4·7H2O and MnSO4·H2O are mixed evenly to form solution B; solution B is added dropwise to solution A and stirred evenly to obtain a first mixed solution.
[0076] 0.2 wt % of pretreated carbon nanotubes were added to the first mixed solution to obtain a second mixed solution.
[0077] (3) Preparation of dual-modified LFMMP-CNTs composites by hydrothermal reaction:
[0078] The second mixed solution was poured into a 100 ml polytetrafluoroethylene liner, sealed in a stainless steel reactor, placed in a muffle furnace and kept at 180° C. for 10 h at a heating rate of 5° C. / min to obtain the product.
[0079] The precipitate in the product was obtained, and the precipitate was washed three times with deionized water and ethanol respectively and centrifuged. Finally, a 15 wt % sucrose (0.614 g / ml) solution of the positive electrode material was added and mixed evenly.
[0080] The obtained product was dried in an oven at 60°C; the obtained product was calcined at 650°C for 2h under an inert atmosphere, and the dual-modified positive electrode material LFMMP-CNTs was obtained after the tubular furnace was naturally cooled.
[0081] Comparative Example
[0082] This comparative example is modified to prepare LFMMP cathode material by solvent thermal method only. The chemical formula of the cathode material is LiFe 0.2 Mn 0.8 PO4, the specific preparation steps are as follows:
[0083] Weigh 30 mmol of LiOH, 11 mmol of H3PO4, 2 mmol of FeSO4·7H2O, and 8 mmol of MnSO4·H2O; dissolve LiOH in a mixed solution of 2 ml of water and 20 ml of ethylene glycol; disperse H3PO4 in 20 ml of ethylene glycol, and dissolve FeSO4·7H2O in 10 ml of ethylene glycol; disperse MnSO4·H2O in a mixed solution of 3 ml of water and 10 ml of ethylene glycol.
[0084] The H3PO4 solution was added dropwise to the LiOH solution to form solution A; FeSO4·7H2O and MnSO4·H2O were mixed evenly to form solution B; solution B was added dropwise to solution A, stirred evenly, and a mixed solution was obtained.
[0085] The mixed solution was poured into a 100 ml polytetrafluoroethylene liner, sealed in a stainless steel reactor, and placed in a muffle furnace and kept at 180 °C for 10 h with a heating rate of 5 °C / min.
[0086] The precipitate in the product was obtained, and the precipitate was washed three times with deionized water and ethanol respectively and centrifuged. Finally, a 15 wt % sucrose (0.614 g / ml) solution of the positive electrode material was added and mixed evenly.
[0087] The product was dried in an oven at 60° C.; the obtained product was calcined at 650° C. for 2 h under an inert atmosphere, and the tube furnace was allowed to cool naturally to obtain the sample LFMMP.
[0088] The LFMMP-CNTs of the embodiment were tested, and the test results are as follows:
[0089] The XRD test results of LFMMP-CNTs are as follows: Figure 1 As shown. Figure 1 It can be seen that the diffraction peak intensity is sharp and there is no impurity peak, indicating that the positive electrode material LFMMP-CNTs has an olivine structure and good crystallinity. The modification has no effect on the synthesis process of the material and no impurities are generated. There is a peak with weaker intensity and wider diffraction angle at 26°, which is the diffraction peak of C, indicating that CNTs have been compounded with the LFMMP positive electrode material.
[0090] Figure 2 This is the SEM image of LFMMP-CNTs. It can be seen that the synthesized LFMMP primary particles are nanoparticles with a size of about 40nm, irregular shape and smooth surface. These nanoparticles grow on the surface of CNTs through in situ synthesis. CNTs are an agglomerate formed by many single carbon nanotubes connected to each other.
[0091] A series of electrochemical tests were conducted on the LFMMP-CNTs of the embodiment and the LFMP of the comparative example to investigate the performance of LFMP and LFMMP-CNTs under different electrochemical performance tests. Figure 3 shown.
[0092] pass Figure 3 It can be seen that the double-modified LFMMP-CNTs material has less capacity decay and higher Coulombic efficiency, indicating that the doped Mg 2+The use of carbon nanotube modification improves conductivity and the contact between active materials and electrolytes, thereby promoting lithium ion transmission and increasing capacity.
[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate material, characterized in that: A mixed solution is prepared by using a magnesium source component, a phosphorus source component, a manganese source component, an iron source component and a lithium source component, the mixed solution is mixed with carbon nanotubes, and the lithium manganese iron phosphate material is generated in situ through a hydrothermal reaction.
2. The method for preparing a magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate material according to claim 1, characterized in that: The molar percentage of the magnesium source component is 0.1-3 mol % of the phosphorus source component.
3. The method for preparing a magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate material according to claim 2, characterized in that: The magnesium source component includes at least one of magnesium sulfate, magnesium carbonate, and magnesium acetate.
4. The method for preparing a magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate material according to claim 1, characterized in that: Taking the mass of the theoretically generated lithium manganese iron phosphate material as 100%, the mass percentage of the carbon nanotubes is 0.05 wt % to 2 wt %.
5. The method for preparing a magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate material according to any one of claims 1 to 4, characterized in that: The lithium source component includes at least one of lithium carbonate, lithium acetate, lithium hydroxide, and lithium dihydrogen phosphate; the phosphorus source component includes at least one of phosphoric acid, ammonium dihydrogen phosphate, and lithium dihydrogen phosphate; the manganese source component includes at least one of manganese oxalate, manganese sulfate, and manganese acetate; and the iron source component includes at least one of ferrous oxalate, ferrous acetate, and ferrous sulfate; wherein the molar ratio of lithium to phosphorus is 1:1 to 3:1, and the molar ratio of the manganese source to the iron source is 5:5 to 9:
1.
6. The method for preparing a magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, adding the phosphorus source solution dropwise to the lithium source solution to obtain solution A; S2, mixing the iron source solution, the magnesium source solution and the manganese source solution to obtain solution B; S3, adding the solution B dropwise to the solution A to obtain a first mixed solution, and adding the carbon nanotubes to the first mixed solution to obtain a second mixed solution; S4, heating the second mixed solution and performing the hydrothermal reaction to obtain a reactant; S5, washing, drying and grinding the precipitate in the reactant to obtain the lithium manganese iron phosphate powder; S6. Sintering the lithium iron manganese phosphate powder to obtain the lithium iron manganese phosphate material.
7. The method for preparing a magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate material according to claim 6, characterized in that: In step S4, the hydrothermal reaction is to introduce the second mixed solution into a polytetrafluoroethylene liner, heat and react in a sealed stainless steel environment to obtain the reactant; the heating temperature is 160-200° C., and the time is 8-16 hours.
8. The method for preparing a magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate material according to claim 6, characterized in that: In step S6, the lithium manganese iron phosphate powder is mixed with a carbon source and then sintered. The sintering conditions are: annealing at a temperature of 500-700° C. for 1-6 hours in an inert atmosphere.
9. A magnesium-doped and carbon nanotube-modified lithium manganese iron phosphate material, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. A lithium battery, characterized in that: The positive electrode material of the lithium battery is the lithium iron manganese phosphate material as claimed in claim 9.
Citation Information
Patent Citations
Metal / carbon nanotube compound doped phosphate ferromanganese material and preparation method thereof
CN106848309A
Preparation method for lithium iron manganese phosphate positive electrode material
CN107128892A
Positive electrode material and preparation method thereof, positive plate and lithium ion battery
CN117691067A
Modified lithium iron manganese phosphate positive electrode material, preparation method thereof and lithium ion battery
CN119943946A
Cited By
Lithium manganese iron phosphate positive electrode material for lithium secondary battery and preparation method of lithium manganese iron phosphate positive electrode material
CN121076122A
A lithium manganese iron phosphate cathode material for lithium secondary batteries and a method for preparing the same
CN121076122B